2015
DOI: 10.4137/sart.s23506
|View full text |Cite
|
Sign up to set email alerts
|

To Cause Harm and to be Harmed by Others: New Perspectives on Alcohol's Harms to Others

Abstract: OBJECTIVETo examine how sociodemographic factors and alcohol consumption are related to a four-way typology of causing harm to others and/or being harmed by others’ and one’s own drinking.DATA AND METHODSData from the 2011 Danish national survey (n = 2,569) were analyzed with multi nomial logistic regression.RESULTSYounger age and heavy drinking were significant correlates of both causing harm and being harmed. Women and better educated respondents were more likely to report negative effects on relationship an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…Regarding the methods for data collection, a previous study indicates that the level of self-reported harm from others’ drinking may be higher in surveys using telephone interviews than in surveys using the Web. 30 However, based on the authors’ general inspection, there was no systematic variation between data collection methods and level of harm between the studies in our comparison.…”
Section: Discussionmentioning
confidence: 83%
“…Regarding the methods for data collection, a previous study indicates that the level of self-reported harm from others’ drinking may be higher in surveys using telephone interviews than in surveys using the Web. 30 However, based on the authors’ general inspection, there was no systematic variation between data collection methods and level of harm between the studies in our comparison.…”
Section: Discussionmentioning
confidence: 83%
“…Future U.S. research should examine differences by age and residence status to assess whether AHTO perpetrated by known drinkers are more detrimental for younger victims or for those co-habiting with the perpetrator, as well as whether recurrent harms are associated with even worse outcomes for victims. Another interesting question is whether alcohol-related harms are reciprocal within dyads—that is, are those harmed by other drinkers also perpetrating alcohol-related harms themselves (Seid, Grittner, Greenfield, & Bloomfield, 2015)—and this area deserves further research.…”
Section: Discussionmentioning
confidence: 99%
“…al, 2011) (Bellis et al, 2015;Greenfield et al, 2009;Seid, Grittner, Greenfield, & Bloomfield, 2015). 과 음자나 음주 문제를 이미 경험하고 있는 사람 또는 술집이 나 술파는 음식점을 자주 가는 사람들이 간접 음주폐해를 더 많이 경험하게 되는데 (Bellis et al, 2015;Greenfield et al, 2009;Seid et al, 2015), 이는 술을 자주, 많이 마심으로 (Bellis et al, 2015;Greenfield et al, 2009 Newton, Barrett, Swaffield, & Teesson, 2014 …”
Section: 최근 들어 미국 호주 유럽 등을 중심으로 음주의 간접unclassified